Antidiabetic Activity Of Cassia Occidentalis L., In Streptozotocin-Induced Diabetic Rats: A Dose Dependent Study - S. EMMANUEL,; M.SHEEBA RANI,; M. RAJA SREEKANTH, (International Journal of Pharma and Bio Sciences, 2010)
Cassia occidentalis Linn. is extensively used in the indigenous and folklore medicine systems to treat several illnesses. However adequate characterization of hypoglycemic activity of C.occidentalis has not yet been done. The scientific evaluation of its hypoglycemic activity was, therefore, explored and also compared with the effect of a standard hypoglycemic drug, Glibenclamide. In the present study methanol fraction of C.occidentalis leaves (COLMF) was tested against streptozotocin-induced diabetic rats. Adult male albino Wistar rats, weighing 150-200g, were randomized into control and experimental groups. Experiment group rats were induced diabetes by a single intraperitoneal injection of streptozotocin (STZ). Treatment with COLMF at different doses and times following in normal and diabetic rats significantly reduced the blood glucose level to normal in diabetic rats (99.68±3.57). Hemoglobin, glycosylated hemoglobin, hepatic glycogen, lipid peroxidation, antioxidants enzymes (TBARS, HP, SOD, CAT, GPx VitC,VitE,GSH) and hepatic marker enzymes (ALT, AST,ALP,ACP) were also evaluated in normal and diabetic rats. Oral administration of COLMF significantly and dose-dependently normalized the above mentioned parameters near to normal in STZ-diabetic rats (p<0.05). Histopathological examination showed that COLMF extract protected the pancreatic tissue from STZ-induced damage.